2023
DOI: 10.3389/fmicb.2023.1219692
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for oral health: do they deliver what they promise?

Wannes Van Holm,
Katalina Lauwens,
Pieter De Wever
et al.

Abstract: Probiotics have demonstrated oral health benefits by influencing the microbiome and the host. Although promising, their current use is potentially constrained by several restrictions. One such limiting factor lies in the prevailing preparation of a probiotic product. To commercialize the probiotic, a shelf stable product is achieved by temporarily inactivating the live probiotic through drying or freeze drying. Even though a lyophilized probiotic can be kept dormant for an extended period of time, their viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This supports the idea that probiotics originated from fecal samples are the same as to those found in the mouth (Rohani et al, 2015). In order to establish long-term colonization of probiotics in the oral cavity, a strong and permanent adherence is required to colonization, however, probiotics remain for a short period in the oral cavity, and most of them establish a reversible adherence with cells that can be easily detached (Van Holm et al, 2023).…”
Section: Functional Properties Of Probiotics In the Oral Cavitysupporting
confidence: 73%
“…This supports the idea that probiotics originated from fecal samples are the same as to those found in the mouth (Rohani et al, 2015). In order to establish long-term colonization of probiotics in the oral cavity, a strong and permanent adherence is required to colonization, however, probiotics remain for a short period in the oral cavity, and most of them establish a reversible adherence with cells that can be easily detached (Van Holm et al, 2023).…”
Section: Functional Properties Of Probiotics In the Oral Cavitysupporting
confidence: 73%
“…As an example, in vitro and in vivo studies of L. reuterii against B16F10 melanoma cells were conducted using 10 7 CFU bacterial suspension; the authors indicated that a minimal concentration of 10 6 CFU/mL viable bacteria is necessary for probiotic activity [ 13 ]. In addition, concentrations of 10 8 –10 9 CFU/dose or higher are found in commercial products advertised with probiotic effects [ 25 ]. Molska and Regula reported that, although the optimal concentration of probiotics that should be recommended for cancer treatment or prevention is not yet clearly established, it cannot be low if a successful impact on the host organism is to be expected; the authors mentioned that 10 10 –10 11 CFU/day of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the probiotic supplementation status of patients is unknown. Probiotics have demonstrated oral health benefits by influencing the microbiome and host [ 69 ]. Finally, we identified some members of the oral microbiota that could be used as indicators of disease status.…”
Section: Discussionmentioning
confidence: 99%